β-HPV Infection Correlates with Early Stages of Carcinogenesis in Skin Tumors and Patient-Derived Xenografts from a Kidney Transplant Recipient Cohort - Borgogna, Cinzia; Olivero, Carlotta; Lanfredini, Simone; Calati, Federica; De Andrea, Marco; Zavattaro, Elisa; Savoia, Paola; Trisolini, Elena; Boldorini, Renzo; Patel, Girish K.; Gariglio, Marisa (Frontiers in Microbiology, 2018)
Many malignancies that occur in high excess in kidney transplant recipients (KTRs) are due to viruses that thrive in the setting of immunosuppression. Keratinocyte carcinoma (KC), the most frequently occurring cancer type in KTR, has been associated with skin infection by human papillomavirus (HPV) from the beta genus. In this report, we extend our previous investigation aimed at identifying the presence of active β-HPV infection in skin tumors from KTRs through the detection of viral protein expression. Using a combination of antibodies raised against the E4 and L1 proteins of the β-genotypes, we were able to visualize infection in five tumors [one keratoacanthoma (KA), three actinic keratosis (AK) and one seborrheic keratosis (SK)] that were all removed from two patients who had been both transplanted twice, had developed multiple KC, and presented with a long history of immunosuppression (>30 years). These infected tissues displayed intraepidermal hyperplasia and increased expression of the ΔNp63 protein, which extended into the upper epithelial layers. In addition, using a xenograft model system in nude mice displaying a humanized stromal bed in the site of grafting, we successfully engrafted three AKs, two of which were derived from the aforementioned KTRs and displayed β-HPV infection in the original tumor. Of note, one AK-derived xenograft, along with its ensuing lymph node metastasis, was diagnosed as squamous cell carcinoma (SCC). In the latter, both β-HPV infection and ΔNp63 expression were no longer detectable. Although the overall success rate of engrafting was very low, the results of this study represent the first proof-of-concept that β-HPV+ and ΔNp63+ intraepidermal hyperplasia can indeed progress to an aggressive SCC able to metastasize. Consistent with a series of reports attributing a causative role of β-HPV at early stages of skin carcinogenesis through ΔNp63 induction and increased keratinocytes stemness, here we provide in vivo evidence that these events are also occurring in the affected skin of KTRs. Due to these β-HPV-driven molecular pathways, the nascent tumor cell is able to acquire a high enough number of carcinogenic insults that its proliferation and survival will eventually become independent of viral gene expression.